Dominant Masculinities and the Lure of the Rural Idyll in The King of Bangkok - Harrison, Rachel (The Journal of the Siam Society, 2023)
This article provides a critical engagement with The King of Bangkok, a 2021 graphic novel by Claudio Sopranzetti, Sara Fabbri and Chiara Natalucci. The novel deploys an original mode of presenting detailed ethnographic research, and makes extensive use of contemporary imagery such as Thai movies including Pen-ek Ratanaruang’s Monrak Transistor (2001). The authors grapple with the complexities of telling a story covering a fifty-year period of Thai politics to a foreign readership outside the academic realm. As a graphic novel, the work falls under the hyper-masculine influence of the “comic book” form, with its traditional emphasis on the male super-hero, including a troubling tendency to personify Bangkok as threateningly female, and to play down the significance of women, especially in the Red-Shirt movement. This stands in contrast to contemporary Arab feminist writers of graphic novels on protest and uprising. Given that the Thai translation of the work as Ta sawang (Open Eyed, or Awakened) was very popular, what does the novel’s final resolution imply for the political “awakening” of the mass? And how does this text compare with key Thai fictional radicals and anti-heroes from the novels and short stories of 20th-century Leftist writers such as Siburapha, Seni Saowaphong and Wat Wanlyangkun?